2017
DOI: 10.1080/1828051x.2017.1408435
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory characteristics of meat from lambs fed diets containing mulberry hay

Abstract: The aim of this study was to evaluate the physicochemical and sensory characteristics of the of meat lamb fed diets containing 0%, 12.5%, and 25.0% mulberry hay (total diet). Twenty-fourÎlede-France lambs in the feedlot at an average age of 60 days and 15 kg body weight were allocated to individual stalls and slaughtered at 32 kg BW. Mulberry hay inclusion in the diet did not affect the meat pH 45 min (6.45) and 24 h (5.70) after slaughter. Average luminosity (L Ã), red intensity (a Ã), and yellow intensity (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The meat pH values were close to the 6.70 and 5.60 found by Campos et al [36] and the 6.45 and 5.70 reported by Cirne et al [37], at 0 and 24 h after slaughter, respectively. Thus, the pH results of the present study indicate that there possibly was a typical development of rigor mortis and the inexistence of pre-slaughter stress [38][39][40], suggesting the absence of alterations in meat quality [41].…”
Section: Physicochemical and Centesimal Compositionsupporting
confidence: 88%
“…The meat pH values were close to the 6.70 and 5.60 found by Campos et al [36] and the 6.45 and 5.70 reported by Cirne et al [37], at 0 and 24 h after slaughter, respectively. Thus, the pH results of the present study indicate that there possibly was a typical development of rigor mortis and the inexistence of pre-slaughter stress [38][39][40], suggesting the absence of alterations in meat quality [41].…”
Section: Physicochemical and Centesimal Compositionsupporting
confidence: 88%
“…As a result, by altering the dietary energy density, the intramuscular and intermuscular fat contents can be balanced [ 8 ]. Mulberry silage contains a high fat content as well as secondary compounds that may improve animal health and meat quality, making it a great potential as an excellent feed resource [ 43 , 44 , 45 ]. In this study, it was found that the replacement of maize silage with mulberry silage in diet significantly increased the EE content in longissimus dorsi muscles of Hu lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep provided 1.15 percent of total meat in Bangladesh, with 12.02 thousand metric tons of meat produced annually (DLS, 2022). The lamb meat is one of the best options for consumers for which they are willing to pay high; however, it fails in gaining market space due to the lack of standardization and quality when it reaches to the consumer (Cirne et al, 2018). Meat quality and price are affected by physiochemical properties.…”
Section: Introductionmentioning
confidence: 99%